Enantioselective carbenoid insertion into C(sp3)–H bonds - Santiago, J. V.; Machado, A. H. L. (Beilstein Journal of Organic Chemistry, 2016)
The enantioselective carbenoid insertion into C(sp3)–H bonds is an important tool for the synthesis of complex molecules due to the high control of enantioselectivity in the formation of stereogenic centers. This paper presents a brief review of the early issues, related mechanistic studies and recent applications on this chemistry area.
Keywords: C–H activation; chiral catalysis; diazo compounds; total synthesis